2020
DOI: 10.1108/vjikms-10-2019-0161
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge sharing to support climate change adaptation in Zimbabwe

Abstract: Purpose Knowledge sharing for evidence-based climate change adaptation is key to reducing vulnerabilities. The disastrous effects of the recent tropical cyclone Idai in Zimbabwe’s eastern highlands, whereby lives and livelihoods were destroyed, calls for fundamental rethinking on how knowledge sharing can be useful in reducing vulnerabilities. This study aims to examine how knowledge sharing practices among selected climate action organisations can support positive results in evidence-based climate change adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The emphasis, therefore, is that as great as stakeholder involvement seems in an intervention, their possession of the right knowledge can result in the right decision and compliance with the rules of engagement through the circulation of the right knowledge and the right time among stakeholders (Chisita & Fombad, 2020 ). Available records from tertiary sources revealed that some residents only attend the hospital when the virus is already at an advanced stage with severe symptoms.…”
Section: Further Discussion On the Identified Issues In The Palliativmentioning
confidence: 99%
“…The emphasis, therefore, is that as great as stakeholder involvement seems in an intervention, their possession of the right knowledge can result in the right decision and compliance with the rules of engagement through the circulation of the right knowledge and the right time among stakeholders (Chisita & Fombad, 2020 ). Available records from tertiary sources revealed that some residents only attend the hospital when the virus is already at an advanced stage with severe symptoms.…”
Section: Further Discussion On the Identified Issues In The Palliativmentioning
confidence: 99%
“…The predominant focus of the AKM articles in KM journals was similar to typical KM areas of interest, considering how to leverage knowledge for business growth, competitive advantage, and organisational improvement, although the former articles considered agricultural organisations and agri-business enterprises. 10 out of the 12 mainstream KM studies were conducted in structured organisational settings(Chisita & Fombad 2020;Gardeazabal et al, 2021;Ahmed & Newton, 2005), across inter-organisational settings(Fait et al 2019; Garcia- Villaverde et al 2008; O'Connor & Kelly 2007) or in institutional settings that bear resemblances with organisations such as a cooperative(Galindo 2007), a network (De Bernardi et al 2021) and a project(Feng et al 2009). The operational context in such structured organisational settings allowed managers/leaders to identify areas where knowledge processes can be leveraged and identify tools and techniques that coujld be used to reinforce the application of knowledge, whether consciously or unconsciously.…”
mentioning
confidence: 99%